1995
DOI: 10.1200/jco.1995.13.11.2737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of menopausal symptoms among women with a history of breast cancer and attitudes toward estrogen replacement therapy.

Abstract: Vasomotor symptoms have a significant impact on the quality of life of breast cancer patients. Clinical trials to determine the safest and the most effective ways to relieve these symptoms are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
181
4
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(205 citation statements)
references
References 35 publications
12
181
4
5
Order By: Relevance
“…In addition, while the literature on risk factors for insomnia in breast cancer remains relatively new [4], there are data suggesting the importance of vasomotor symptoms vis-a`-vis insomnia in studies of breast cancer [8,54] and menopausal women in general [38][39][40][41][42][43]. Vasomotor symptoms are well-established sequelae of the climacteric, whether natural or treatment induced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, while the literature on risk factors for insomnia in breast cancer remains relatively new [4], there are data suggesting the importance of vasomotor symptoms vis-a`-vis insomnia in studies of breast cancer [8,54] and menopausal women in general [38][39][40][41][42][43]. Vasomotor symptoms are well-established sequelae of the climacteric, whether natural or treatment induced.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia affects approximately 20% of adults in the general population and is more common in cancer patients [1] (prevalence estimates in cancer range from 23−61% [2][3][4][5]) and may be particularly common in women who have undergone treatment for breast cancer [6,7]. For example, a recent report found that of women who had completed treatment for breast cancer reported non-specific sleep problems [3,7], 19% met criteria for insomnia syndrome which was chronic in 95% of cases [3,7], and 23−44% reported insomnia 2−6 years after receiving their breast cancer diagnosis [8,9]. Despite its elevated prevalence and potential impact on quality of life (QOL) [4,7,10,11] insomnia in cancer has only recently begun to receive attention and little is known about risk factors for insomnia in this population [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 25%-50% of all prescriptions written for patients with cancer are for hypnotics [7,8]. Additionally, sleep disruptions can persist in cancer survivors for many years after diagnosis and completion of treatment, making it one of the most pervasive problems faced by patients with cancer [9,10].…”
Section: Thementioning
confidence: 99%
“…T he use of estrogen and estrogen-progesterone combinations for hormone replacement therapy (HRT) is becoming increasingly common among women, mainly for the alleviation of menopausal symptoms 1 and the prevention of osteoporosis. [2][3][4][5] Although reports on the efficacy of HRT to treat coronary heart disease are mixed, 6 -8 it is used for the long-term prevention of coronary heart disease in women.…”
mentioning
confidence: 99%